Women Within the Circle of Doctrine and Profession: A Study on the Analysis of Women's Professions in Desa Klumpit, Kudus, Central Java - Afifah, Anisa Nurul (An-Nida', 2023)
This study discusses women in all professions (occupations) and their relevance in today's times from an Islamic perspective. In a patriarchal culture, women are initiated to work as housewives. Women are considered inferior and are always positioned below men without being allowed to fight for their rights. However, along with the times, many figures gave rise to the feminist movement so that women began to be able to fight for their rights. The purpose of this article is to narrate religious teachings related to women and aspects that can be reached by women in their profession according to Islamic teachings.  This paper uses a qualitative-phenomenological method that observes the lives of women in Klumpit Village, Kudus. It also uses field research by interviewing two religious leaders and a factory worker's mother. This article uses Fatima Mernissi's gender theory which states that freedom of human rights to work is shared by all genders. In addition, it also uses the theory of Abraham Maslow which states that needs are a primary aspect of human life to fulfil life standards. This article concludes that in Klumpit Village, Kudus, women have the main duty as housewives, but women are also not prohibited from having professions other than housewives. Islam doctrinally also does not prohibit women from being active in the public sphere. Through the application of Islamic law that has been determined and then practised in accordance with the times, it should be a solution for women so that they can make efforts to reduce the negative impacts arising from the profession they do and of course still get pleasure, blessings, and benefits. Abstrak: Kajian ini membahas tentang perempuan dengan segala profesi (pekerjaan) dan relevansinya di zaman sekarang dalam perspektif Islam. Dalam budaya patriarki perempuan diinisiasi berprofesi sebagai ibu rumah tangga. Perempuan dianggap rendah dan selalu diposisikan paling bawah dari laki-laki tanpa boleh memperjuangkan haknya. Namun seiring perkembangan zaman banyak tokoh yang memunculkan gerakan feminisme sehingga perempuan mulai dapat memperjuangkan hak-haknya. Tujuan artikel ini ialah menarasikan ajaran agama terkait perempuan dan aspek yang bisa dijangkau perempuan dalam berprofesi sesuai ajaran Islam. Tulisan ini menggunakan metode kualitatif-fenomenologis yang mengamati kehidupan perempuan di Desa Klumpit, Kudus. Selain itu juga melalui penelitian lapangan dengan mewawancarai dua tokoh agama dan ibu karyawan pabrik. Artikel ini menggunakan teori gender Fatima Mernissi yang menyatakan bahwa kebebasan hak asasi bekerja itu dimiliki oleh semua gender. Disamping itu juga menggunakan teori dari Abraham Maslow yang menyatakan bahwa kebutuhan merupakan aspek primer dalam kehidupan manusia untuk memenuhi hajat hidup. Artikel ini menyimpulkan bahwa masyarakat Desa Klumpit, Kudus, perempuan mempunyai tugas utama sebagai ibu rumah tangga, namun perempuan juga tidak dilarang untuk berprofesi selain ibu rumah tangga. Islam secara doktrinal juga tidak melarang perempuan untuk beraktivitas di ranah publik. Melalui penerapan syariat Islam yang sudah ditentukan kemudian dipraktikkan sesuai dengan zaman, hendaknya menjadi solusi perempuan agar dapat melakukan upaya untuk mengurangi dampak negatif yang ditimbulkan dari profesi yang dikerjakan dan tentunya tetap mendapat ridha, berkah, dan manfaat.